Treatment According to a Comprehensive Molecular Profiling Can Lead to a Better Outcome in Heavily Pretreated Patients With Metastatic Cancer: Data of a Pooled Analysis. Issue 2 (March 2019) - Seeber, Andreas; Chahine, Georges; Nasr, Fadi; Dean, Andrew; Miranova, Mira; Jameson, Gayle; Robert, Nicholas; Gastl, Guenther; Zwierzina, Heinz
Abstract : Purpose: Improvements in systemic treatment have led to a prolongation of survival and quality of life in patients with metastatic tumors in recent years. However, despite this improved standard of care, it is expected that the progression-free survival (PFS) for patients with refractory cancers will continue to decline over subsequent therapy lines. In those patients, studies and meta-analyses showed that treatment based on multiplatform molecular profiling (MMP) of tumor tissue may derive a clinical benefit. The aim of this study was to analyze if molecular-based therapy may prolong PFS compared with the PFS of the immediately prior therapy. Methods: We pooled clinical data of 140 patients treated within 3 recently conducted pilot studies and included an additional 21 patients who were treated within the ongoing ONCO-T-PROFILE program. The PFS of the molecular-based treatment was compared with the PFS of the previous therapy using Kaplan-Meier curves. Results: In heavily pretreated cancer patients, the PFS could be significantly improved using molecular-based treatment options (120.0 vs. 89.5 days). More than 50% of patients showed a clinical benefit from MMP-guided therapy as defined by a PFS ratio of 1.3 or greater. Conclusions: We conclude that pretreated cancer patients can benefit from incorporation of molecular profiling, as demonstrated by not only an increase of the PFS ratio but also PFS. Further randomized trials in specific tumor subtypes may help establish specific patient populations who might benefit most from MMP guidance.